Media Sosial sebagai Sarana Pembelajaran Membentuk Karakter Pemimpin Islami pada Anak melalui Forum Komunikasi Anak Kabupaten Trenggalek - Mutrofin; Delvi Nur Syafiah; Syahrani Amelia Putri (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2025)
This study examines how leadership character is developed during childhood through the Children Communication Forum in Trenggalek Regency, and how social media is utilized as a platform for expression and learning. From childhood to adolescence, adulthood, and parenthood, every individual undergoes a growth process. Early childhood requires proper Islamic character education to support successful development in the future. One of the key traits that may emerge is Islamic leadership. The purpose of this study is to explore how early personality development influences the creation of a better future. Even when children are given full control of an organization, managing it and sharing its activities via social media can help them develop leadership and communication skills, as well as boost their confidence. This research employs a qualitative method with a sociological approach. Data were collected through observation, interviews, documentation of forum activities, and monitoring the forum's official social media accounts. The study is based on the theory of social leadership, which asserts that leaders are not born but made through preparation, education, and training. With the right guidance and opportunities for self-expression, including through social media, anyone can choose to become a leader.